Adenotonsillectomy in high risk patients: Hematologic abnormalities and COVID-19 considerations - Ryan Ruiz (KeAi Communications Co., Ltd., 2021)
Adenotonsillectomy is one of the most common surgical procedures performed by otolaryngologists. It is vital that surgeons are aware of the risks in performing this surgery especially during the COVID-19 pandemic and in children with hematologic disorders. In this review we describe common hematologic disorders often noted in pediatric patients undergoing this procedure, as well as proper screening and management of these patients. In addition, we also address the impact of the COVID-19 pandemic and some measures to help mitigate the risks of this procedure during this time.